THE PHENOMENA OF VIOLENCE TOWARDS WOMEN AND CHILDREN IN MODERN INDONESIAN LITERATURES - I Gusti Ayu Agung Mas Triadnyani (International Conference on Languages and Arts, 2014)
This paper examines acts of violence on women and children in Indonesian literatures. In fact, the issue of such a violence has recently been one of the Indonesian media’s hot topics. Therefore, this may indicatethe environmental condition showing the higher oppression suffered by women and children. In the perspective of the progress of technology, there isstill a break of human basic rights.For limiting the topicthe writer has isolated three writers to discuss. They are Djenar Maesa Ayu (Nayla, 2005), Dewi Sartika (Dadaisme, 2006) and Kadek Sonia Piscayanti (Karena Saya Ingin Berlari, 2007). Literary critics, such as Faruk, Manneke Budiman, and Sapardi Djoko Damono, (Jurnal Prosa, No.4/2004) thought that the birth ofwoman writer was the impact of industrialization.The amount of woman readers has been graduallyrising and women become the prime readers of literature in modern era. But, along with the rising of capability of readers, these women also tend to write any works about themselves. As women, they surely have  different point of view and sensibility from the men do, because those women see themselves and the surroundings due to violence experienced by themselves as well. Through the study of those three writers whose cultural backgrounds are different, this paper exposes theirown characteristic sights about the phenomenon of violence against women and children. The result of this research might hopefully open the consciousness of people to  better understandings of women and children.   Key words: violence, women, child, public, domestic